Organoelectrocatalytic cyclopropanation of alkenyl trifluoroborates with methylene compounds - Wei Yi; Peng-Cheng Xu; Tianyu He; Shuai Shi; Shenlin Huang (Nature Communications)
Abstract Cyclopropanes are not only privileged motifs in many natural products, agrochemicals, and pharmaceuticals, but also highly versatile intermediates in synthetic chemistry. As such, great effort has been devoted to the cyclopropane construction. However, novel catalytic methods for cyclopropanation with two abundant substrates, mild conditions, high functional group tolerance, and broad scope are still highly desirable. Herein, we report an intermolecular electrocatalytic cyclopropanation of alkenyl trifluoroborates with methylene compounds. The reaction uses simple diphenyl sulfide as the electrocatalyst under base-free conditions. And thus, a broad scope of various methylene compounds as well as vinyltrifluoroborates is demonstrated, including styrenyl, 1,3-dienyl, fluorosulfonyl, and base-sensitive substrates. Preliminary mechanistic studies are presented, revealing the critical role of the boryl substituent to facilitate the desired pathway and the role of water as the hydrogen atom source.